Level of HR proficiency in small and medium sized organizations in Middle-Hungary Region - Finna, Henrietta; Krajcsák, Zoltán (Marketing & Menedzsment, 2019)
SMEs are not simplified versions of big companies and this true for human resources management skills, staff and practices as well. Duties in human resource management of a small venture generally don't motivate to have an HR department or an expert. Most important duties are carried out mainly owners but usually with no knowledge in this field. In Hungarian HR literature results of human resources management are widely adapted. As a contribution a research has been conducted in which HR activities of SMEs in the Region of Middle-Hungary have been analysed.